Hospital management system / Mary Anne Soosay - Mary Anne, Soosay (2003)
lnternet has often been referred to as the "Information Superhighway". The concept of being able to access information quickly and easily led to the vision of the Internet. With the advancement of information technology and increasing number of users getting connected to the net, various techniques are being employed on the world wide web. It provides sustaining facility accessible to hundreds of million of people worldwide. The medical community is moving toward an environment where automated patient medical records, and electronically interconncted healthcare facilities, are becoming prevalent. The primary reason is that the electronic record, coupled with the electronic networking of hospitals, can provide healthcare organizations with more efficient, seamless services, resulting in higher quality care and reduced healthcare costs. A major tenet of such automation, and indeed of healthcare reform as a whole, is the ability to share patient information. With this in mind, the hospital management system intends to provide a similar service to its users and thus creating an information hub that stores and retrieves information pertaining to the patient. The hospital management system will focus on patient related situations while resolving the drawbacks of the conventional method of retrieving user information through loads of paper and manual record.